The self-defense in situations of gender-based violence. Progress and perspectives - Medina Sarmiento, Rosabel Francisca (2023)
Gender violence affects one in three women in the world, it is a social problem that requires comprehensive responses to address it. In the legal sphere, judicial decisions can contribute to providing, through the application of a gender perspective and humanist legal dogmatic interpretation, full access to justice for victims and survivors of violence. In the cases in which they become defendants, a gender-sensitive look is required in the criminal process, especially in terms of assessing the requirements of self-defense and the assessment of the evidence. The research proposes to reflect from the analysis of doctrinal criteria and jurisprudence on the subject.